Pleural tuberculosis: is radiological evidence of pulmonary-associated disease related to the exacerbation of the inflammatory response? - Leila Antonangelo; Francisco S. Vargas; Juliana Puka; Márcia Seiscento; Milena M. P. Acencio; Lisete R. Teixeira; Ricardo M. Terra; Roberta K. B. Sales (Clinics)
OBJECTIVE: Pleural tuberculosis is the most frequently occurring form of extra pulmonary disease in adults. In up to 40% of cases, the lung parenchyma is concomitantly involved, which can have an epidemiological impact. This study aims to evaluate the pleural and systemic inflammatory response of patients with pleural or pleuropulmonary tuberculosis. METHODS: A prospective study of 39 patients with confirmed pleural tuberculosis. After thoracentesis, a high resolution chest tomography was performed to evaluate the pulmonary involvement. Of the 39 patients, 20 exhibited only pleural effusion, and high resolution chest tomography revealed active associated-pulmonary disease in 19 patients. The total protein, lactic dehydrogenase, adenosine deaminase, vascular endothelial growth factor, interleukin-8, tumor necrosis factor-α, and transforming growth factor-β1 levels were quantified in the patient serum and pleural fluid. RESULTS: All of the effusions were exudates with high levels of adenosine deaminase. The levels of vascular endothelial growth factor and transforming growth factor-β1 were increased in the blood and pleural fluid of all of the patients with pleural tuberculosis, with no differences between the two forms of tuberculosis. The tumor necrosis factor-α levels were significantly higher in the pleural fluid of the patients with the pleuropulmonary form of tuberculosis. The interleukin-8 levels were high in the pleural fluid of all of the patients, without any differences between the forms of tuberculosis. CONCLUSION: Tumor necrosis factor-α was the single cytokine that significantly increased in the pleural fluid of the patients with pulmonary involvement. However, an overlap in the results does not permit us to suggest that cytokine is a biological marker of concomitant parenchymal involvement. Although high resolution chest tomography can be useful in identifying these patients, the investigation of fast acid bacilli and cultures for M. tuberculosis in the sputum is recommended for all patients who are diagnosed with pleural tuberculosis.